Incidence of sudden unexpected death in an adult outpatient cohort with epilepsy at a tertiary referral centre. Issue 4 (April 1995) - Nashef, L; Fish, D R; Sander, J W; Shorvon, S D
Abstract : Overall mortality, incidence of sudden unexpected death, and cause of death were determined in 601 adult outpatients with epilepsy at a tertiary referral centre. The patients were followed up from 1990 to 30 June 1993. There were 24 deaths among the 601 patients (1849 patient years) with a standardised mortality ratio of 5.1 (95% confidence interval 3.3-7.6) of which 14 were related to epilepsy. Underlying disease of which epilepsy was a symptom accounted for four deaths only. An incidence of sudden deaths (including seizure related) was of the order of 1:200/year. In conclusion, excess mortality in chronic epilepsy is more likely to be related to the epilepsy itself than to underlying pathology. The relatively high incidence of sudden deaths found in this hospital based cohort has important implications for patient management.